The criminality of mentally disordered offenders - Hodgins, Sheilagh (Criminal justice and behavior, 1993)
Although many incarcerated offenders suffer from major mental disorders, little is known about their criminality. The present study addressed two hypotheses: (a) mentally disordered inmates, as compared to nondisordered inmates, would have a history of more convictions and more convictions for violent offenses; (b) among the mentally disordered, those with co-occurring antisocial personality disorder (APD) would have more total convictions and more convictions for violent offenses. A representative sample of male inmates of the penitentiaries situated in Quebec were examined. Mental health was assessed using the Diagnostic Interview Schedule. Comparisons were made between the 107 inmates who had suffered at least one episode of a major mental disorder and the other 349 inmates. The first hypothesis was not supported, as it was found that the criminal careers of mentally disordered and nondisordered inmates differed little. However, the hypothesis that APD combined with major mental disorder increases the risk of crime was supported; the risk of violent crime, however, was not increased. The results argue for the existence of two distinct groups of mentally disordered inmates